Faktor-faktor Penentu Penggunaan Websites sebagai Media Pembelajaran Matakuliah Konsentrasi Pemasaran (Perspektif Theory of Reasoned Action dan Theory of Technology Acceptance) - Murwani, F. Danardana (Universitas Brawijaya, Indonesia, 2008)
The research was intended to verify the determinants of websites usage as learning media based on Theory of Reasoned Action (TRA) and Theory of Technology Acceptance (TTA). The population was all bachelor degree students of Economic Faculty at State University of Malang, which studied major subjects of marketing at 2nd semester in 2007/2008. The population size was 344 students. The Davis-Cosenza's formula was used to determine the sample size of 183 students. The Likert-five point scale was used as a research instrument. Furthermore, the data were analyzed by structural equation modeling. The findings fully confirmed the measurement model of TRA and TTA, and the structural model of TRA, while the structural model of TTA was confirmed by adjustment of its measurement model.